A Pandemia de Covid-19 no Brasil : a pobreza e a vulnerabilidade social como determinantes sociais - Simone Affonso da Silva (Confins, 2021)
About a year after the notification of the first case of Covid-19 in the world, we have a very bad scenario in Brazil, since the country occupies, respectively, the 3rd and 2nd positions in the ranking of countries with the highest number of confirmed cases and with the highest number of deaths. In this article we will analyse the Covid-19 pandemic from the perspective of social determinants of health, in particular some risk factors to which a large part of the Brazilian population is exposed: poverty and social vulnerability. Through bibliographic and documentary analysis and spatial analysis, we examined: (i) the general picture of pre-existing socio-spatial inequalities, (ii) the diagnoses related to the dynamics of the Covid-19 pandemic, (iii) the set of measures adopted by the Brazilian State; and (iv) the issue of government planning, its potential, limits and challenges in the current situation of the Covid-19 pandemic. Thus, we consider whether and how the strategies and measures adopted in Brazil to mitigate poverty and social vulnerability in the context of the Covid-19 pandemic take into account socio-spatial inequalities, meeting the demands of the most vulnerable population, territories and regions. We conclude that the lack of adherence between the measures adopted to face the pandemic and the country's social, political, cultural and economic reality is one of the greatest obstacles to overcoming poverty and social vulnerability that has intensified or even created itself in the context of pandemic. However, we argue that the problems in government planning, in part, are due to the political choices of the current Brazilian government - populist, right-wing, conservative and neoliberal -, which denies the seriousness of the disease and minimizes the extent of the pandemic in the country.